Ответы и объяснения

  • 6575
  • почетный грамотей
2013-04-06T17:13:29+00:00

cos6x=cos3x-sin3x
cos^2(3x)-sin^2(3x)=cos3x-sin3x
(cos3x-sin3x)(cos3x+sin3x)-(cos3x-sin3x)=0
(cos3x-sin3x)(cos3x+sin3x-1)=0
cos3x=sin3x    cos3x+sin3x-1=0
tg3x=1              cos3x+sin3x=1
3x=п/4+пk       √2(√2/2cos3x+√2/2sin3x)=1
x=п/12+пk/3   sin(3x+п/4)=√2/2
                           3x+п/4 = (-1)^k п/4+пk
                           3x = (-1)^k п/4 - п/4 + пk
                            x = (-1)^k п/12 - п/12 + пk/3